METHODS OF WORD COMBINATION IN SENTENCE CONSTRUCTION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores various methods of combining words in a sentence, focusing on strategies that enhance clarity, meaning, and style. It covers techniques such as coordination, subordination, apposition, parenthesis, ellipsis, conjunctions of comparison, and correlative conjunctions, offering readers practical insights into how sentence structure influences communication. The article explains each technique with clear examples, demonstrating how they can be used to connect words, phrases, and clauses effectively. Additionally, it highlights more advanced strategies like inversion, serial commas, and juxtaposition, which add emphasis, clarity, and contrast to sentences. Through this exploration, the article aims to help writers and speakers refine their sentence construction, leading to more effective and compelling communication.